2023
DOI: 10.7717/peerj.15538
|View full text |Cite
|
Sign up to set email alerts
|

Restoring South African subtropical succulent thicket using Portulacaria afra: exploring the rooting window hypothesis

Abstract: Drought prone, arid and semi-arid ecosystems are challenging to restore once degraded due to low levels of natural recruitment and survival of reintroduced plants. This is evident in the restoration of degraded succulent thicket habitats in the Albany Subtropical Thicket Biome located in South Africa. The current restoration practice for this ecosystem focuses predominantly on reintroducing Portulacaria afra L. Jacq., which is naturally dominant in terms of cover and biomass, but largely absent in regions degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The findings presented here ( i.e., that source location impacts plant condition and consequently root development in P. afra cuttings) have important implications for succulent thicket restoration initiatives. Cutting source location effects have not been considered in P. afra planting efforts to date, and as shown here (initially demonstrated in Galuszynski et al, 2023 ) may play an important role in unrooted cutting establishment and survival, particularly under field and nursery conditions. As previously noted, planting of unrooted P. afra cuttings is an unreliable restoration practice ( van der Vyver et al, 2021 ; Mills & Robson, 2017 ).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The findings presented here ( i.e., that source location impacts plant condition and consequently root development in P. afra cuttings) have important implications for succulent thicket restoration initiatives. Cutting source location effects have not been considered in P. afra planting efforts to date, and as shown here (initially demonstrated in Galuszynski et al, 2023 ) may play an important role in unrooted cutting establishment and survival, particularly under field and nursery conditions. As previously noted, planting of unrooted P. afra cuttings is an unreliable restoration practice ( van der Vyver et al, 2021 ; Mills & Robson, 2017 ).…”
Section: Discussionmentioning
confidence: 81%
“…A biome-wide field experiment—consisting of 330 plots to test the viability of various planting treatments using unrooted P. afra cuttings—revealed that cutting survival was affected by stem diameter ( i.e., larger cuttings established more readily than small cuttings), uncontrolled herbivory, and planting into the incorrect habitat ( van der Vyver et al, 2021 ). However, the reported variability in survival may also be due to the condition of the source populations, which has the potential to override any treatment effects ( Galuszynski et al, 2023 ). While cutting size and planting habitat can be easily managed, there is currently no clear method for identifying optimal material to source cuttings for restoration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not watering cuttings for 28 days after planting had minor effects on their growth. However, differences in health and condition of individual parent plants had an overriding influence on root growth (Galuszynski et al, 2023).…”
Section: Timing Of Watering After Planting Affects Root Development I...mentioning
confidence: 99%